Core-shell Fe@FexOy nanoring system: A versatile platform for biomedical applications. (January 2022) - Galeano-Villar, Bianca M.; Caraballo-Vivas, Richard J.; Santos, Evelyn C.S.; Rabelo-Neto, Raimundo C.; Gemini-Piperni, Sara; Finotelli, Priscilla V.; Checca, Noemi R.; Dias, Carlos S.B.; Garcia, Flávio
Graphical abstract: Highlights: Two-step preparation of a core@shell (Fe@Fex Oy ) nanotube system allows the tunning of the metallic iron and iron oxide phases. The Fe@Fex Oy nanotubeś magnetic saturation can adjust for a desirable application by varying the synthesis conditions. The Fe@Fex Oy nanotubes have a vortex state, which guarantees low remanence and coercivity. Fe@Fex Oy nanotubes present good biocompatibility for two cells line: HEK and SAOS2. Abstract: Iron oxide (maghemite and magnetite) nanoparticles are the most commonly used magnetic materials in nanomedicine because of their high biocompatibility. However, their low saturation magnetization (60–90 emu/g) limits their applicability. Here, we report a new core–shell (Fe@Fex Oy ) nanoring system, which combines the high magnetic saturation of a metallic iron core (220 emu/g) and the biocompatibility of an iron oxide shell. To produce these nanostructures, hematite (α-Fe2 O3 ) nanorings were annealed in a H2 gas atmosphere for different periods to optimize the amount of metallic iron percentage (δ) in the system. Thus, nanostructures with different magnetic saturation (97 to 178 emu/g) could be obtained; based on their metallic iron content, these particles are labeled as Vortex Iron oxide Particle δ (VIPδ). Micromagnetic simulations confirmed that the VIPδ nanorings exhibit a vortex configuration, guaranteeing low remanence and coercitivity. Moreover, the system shows good biocompatibility in various assays as determined through cell viability measurements performed using two different human cell lines, which were exposed to VIP78% for 24 h. Therefore, VIPδ nanorings combine a magnetic vortex state and biocompatibility with their high magnetic saturation and can thus serve as a platform that can be tuned during the synthesis based on desired biomedical application.